The effects of ultrasound pressure and temperature fields in millisecond bubble nucleation - de Andrade, Matheus Oliveira; Haqshenas, Seyyed Reza; Pahk, Ki Joo; Saffari, Nader (ELSEVIER SCIENCE BV, 2019)
A phenomenological implementation of Classical Nucleation Theory (CNT) is employed to investigate the connection between high intensity focused ultrasound (HIFU) pressure and temperature fields with the energetic requirements of bubble nucleation. As a case study, boiling histotripsy in tissue-mimicking phantoms is modelled. The physics of key components in the implementation of CNT in HIFU conditions such as the derivation of nucleation pressure thresholds and approximations regarding the surface tension of the liquid are reviewed and discussed. Simulations show that the acoustic pressure is the ultimate trigger for millisecond bubble nucleation in boiling histotripsy, however, HIFU heat deposition facilitates nucleation by lowering nucleation pressure thresholds. Nucleation thus occurs preferentially at the regions of highest heat deposition within the HIFU field. This implies that bubble nucleation subsequent to millisecond HIFU heat deposition can take place at temperatures below 100 degrees C as long as the focal HIFU peak negative pressure exceeds the temperature-dependent nucleation threshold. It is also found that the magnitude of nucleation pressure thresholds decreases with decreasing frequencies. Overall, results indicate that it is not possible to separate thermal and mechanical effects of HIFU in the nucleation of bubbles for timescales of a few milliseconds. This methodology provides a promising framework for studying time and space dependencies of the energetics of bubble nucleation within a HIFU field.
Keywords: ACOUSTIC CAVITATION; TISSUE STIFFNESS; SURFACE-TENSION; HISTOTRIPSY; WATER; STABILIZATION; MECHANISMS; FREQUENCY; DYNAMICS; NUCLEI